Effectiveness Interactive Demonstrations Method on Temperature and Calor in the Tenth-Grade Students - Ira Nofita Sari; Dwi Fajar Saputri; Helmiyanti Helmiyanti (STKIP Singkawang, 2020)
This study aims to determine the effectiveness of the interactive demonstration method on the discussion of temperature and heat in the tenth-grade students of the Segedong Number 1 Senior High School. The method used is a pre-experimental design with the design of the one-shot case study. Data collection techniques used in this study include measurement techniques, direct communication techniques, and indirect communication techniques. The data analysis technique used in this study is quantitative data analysis. Based on data analysis, it is known that the average student learning outcomes reached completeness of 86.67%, and is classified as complete in classical, student learning activities classified as good with a percentage of 67.65%, and student responses are classified as very strong with a percentage of 82.58%, so the interactive demonstration method is effective at the temperature and heat of the material in the tenth-grade students of the Segedong Number 1 Senior High School.